2021
DOI: 10.1002/ejic.202100281
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Oxidase‐like Performances of CoxMn3‐xO4 Nanoparticles by Tuning the Mn Content and Decorating Reduced Graphene Oxide

Abstract: Binary transition-metal oxides nanomaterials as oxidase-mimic have attracted great attention, but their catalytic activity and stability remain to be improved, and the underneath mechanism needs to be debated. In this work, Co x Mn 3-x O 4 nanoparticles were prepared in-situ on reduced graphene oxide sheets through a hydrothermal procedure. The morphologies, compositions, and oxidase-like activities of the Co x Mn 3-x O 4 nanoparticles supported on reduced graphene oxide (Co x Mn 3-x O 4 NPs/rGO) were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…The doping ratio also influenced the activity of the NPs, as Zhang et al prepared Co x Mn 3-x O 4 NPs in situ on reduced graphene oxide sheets and then modulated the catalytic activity of the OXD by adjusting the Co/Mn ratio. [77] In another exciting development, Jiang et al synthesized hollow nanoporous carbon skeletons (Au/Co@HNCF) modified with Au/Co bimetallic NPs using a similar thermal cleavage method. [78] By comparing the electrochemically active surface area (ECSA) values of the materials before and after doping, they found that the number of active sites of Au/Co@HNCF was higher than that of Co@NCF, indicating the efficiency of the doping process in enhancing the activity of the NP activity.…”
Section: Multicomponent Synergiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The doping ratio also influenced the activity of the NPs, as Zhang et al prepared Co x Mn 3-x O 4 NPs in situ on reduced graphene oxide sheets and then modulated the catalytic activity of the OXD by adjusting the Co/Mn ratio. [77] In another exciting development, Jiang et al synthesized hollow nanoporous carbon skeletons (Au/Co@HNCF) modified with Au/Co bimetallic NPs using a similar thermal cleavage method. [78] By comparing the electrochemically active surface area (ECSA) values of the materials before and after doping, they found that the number of active sites of Au/Co@HNCF was higher than that of Co@NCF, indicating the efficiency of the doping process in enhancing the activity of the NP activity.…”
Section: Multicomponent Synergiesmentioning
confidence: 99%
“…prepared Co x Mn 3‐x O 4 NPs in situ on reduced graphene oxide sheets and then modulated the catalytic activity of the OXD by adjusting the Co/Mn ratio. [ 77 ] In another exciting development, Jiang et al. synthesized hollow nanoporous carbon skeletons (Au/Co@HNCF) modified with Au/Co bimetallic NPs using a similar thermal cleavage method.…”
Section: Unique Properties Of Co‐based Nanozymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we select layered double hydroxides (LDHs) with positive charge as model nanozymes to study their selective antibacterial activity against G À bacteria. [20][21][22][23][24] Here, we prepared NiCo LDHs nanostructures with tunable composition, morphology, and surface area to obtain the highest antibacterial activity. Using their generated ROS based on their peroxidase-like activity, Ni 4 Co 6 LDHs could effectively kill bacteria.…”
Section: Introductionmentioning
confidence: 99%